ISU PEREMPUAN SEBAGAI STRATEGI KOMUNIKASI POLITIK KAMPANYE CALON DALAM PILKADA - Handoko, Waluyo (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2009)
The role of women in development up to now has not been maximally played although reformation era has opened thespace for women to actively participate.Related to pilkada (local election), women empowerment should be considered as an interesting andimportant issue for campaign. However, based on the cases elaborated in this research, most candidates did not take into account womenempowerment programs as political communication strategy in campaign. There are two reasons which can logically explain thisphenomenon; first, women empowerment issue was not considered as important as other issues which can directly answer the crucial socialproblems such as poverty alleviation, providing job opportunities for unemployment or dealing with expensive fee for education so that noteffective to attract the voters. Second, there was an assumption that sex does not have significant relation with political choice of voters. Itmeans female voters do not always vote for female candidates or candidates focusing on women empowerment programs. Finally, issuesrelated to women role improvement were not much included in campaign materials of either male or female candidates to catch theattention of voters.